Quality Characteristics of Pleurotus sajor-caju Powder: Study on Nutritional Compositions, Functional Properties and Storage Stability (Ciri Kualiti Serbuk Pleurotus sajor-caju: Kajian terhadap Komposisi Zat Pemakanan, Sifat Berfungsi dan Kestabilan Penyimpanan) - Ng, Sze Han; Wan Ahmad, Wan Amir Nizam; Wan Rosli, W. I. (Faculty of Science and Technology, Universiti Kebangsaan Malaysia, 2016)
Pleurotus sajor-caju (PSC) is an oyster mushroom widely consumed in Asian countries and successfully cultivated in Malaysia. This study aimed to determine nutritional compositions, functional properties and storage stability of PSC powder based on storage temperature. Fresh PSC was dried using low heat air blow technique and ground into fine powder. Nutritional analyses of PSC powder were conducted following AOAC methods. Functional properties were also determined accordingly. For storage stability study, four portions of PSC powder were stored at temperature of -20, 4, 25 and 35oC separately, and then studied parameters were investigated at time 0, 3 and 6 months. PSC powder contains appreciable amounts of protein (22.41%), ash (7.79%), dietary fibre (56.99%) and β-glucan (3.32%) but low content in sucrose (0.19%) and fat (2.30%). It also possesses notable functional properties such as water holding capacity, oil holding capacity, swelling capacity and emulsifying activity. Storage stability study showed that PSC powder exhibited lower moisture content and L* colorimetric value. Meanwhile higher water activity level with increasing storage temperature but no significant difference in pH value and microbial counts were detected. Besides, storage temperature at -20, 25 and 35oC jeopardized the original colour properties of PSC powder. The best storage temperature for PSC powder is 4oC. PSC powder has the potential to be a safe and as an alternative dietary fibre rich ingredient in food industry due to its nutritional, functional and storage stability properties. || Pleurotus sajor-caju (PSC) adalah sejenis cendawan tiram yang digunakan di negara Asia secara meluas dan ditanam dengan jayanya di Malaysia. Kajian ini bertujuan untuk menentukan komposisi zat makanan, sifat berfungsi dan kestabilan penyimpanan serbuk PSC berdasarkan suhu penyimpanan. PSC segar dikeringkan dengan menggunakan teknik semburan udara haba rendah dan dikisar sehingga menjadi serbuk halus. Analisis pemakanan serbuk PSC telah dijalankan mengikut kaedah AOAC. Sifat berfungsi juga turut ditentukan. Untuk kajian kestabilan penyimpanan, empat bahagian serbuk PSC telah disimpan pada suhu -20, 4, 25 dan 35oC secara berasingan, dan kemudian parameter tertentu telah dikaji dalam masa 0, 3 dan 6 bulan. Serbuk PSC mengandungi kuantiti protein (22.41%), abu (7.79%), serat makanan (56.99%) dan β-glukan (3.32%) yang tinggi tetapi kandungan sukrosa (0.19%) dan lemak (2.30%) yang rendah. Ia juga mempunyai sifat berfungsi yang ketara seperti muatan simpanan air, muatan simpanan minyak, pembengkakan dan aktiviti mengemulsi. Kajian kestabilan penyimpanan menunjukkan serbuk PSC mempunyai kandungan lembapan dan nilai L* yang lebih rendah. Sementara itu, aktiviti air yang lebih tinggi dengan peningkatan suhu penyimpanan tetapi tiada perbezaan yang ketara pada nilai pH dan kandungan mikrob telah dikesan. Selain itu, suhu penyimpanan pada -20, 25 dan 35oC menjejaskan sifat warna asal serbuk PSC. Suhu penyimpanan yang terbaik untuk serbuk PSC adalah 4oC. Serbuk PSC berpotensi sebagai diet selamat dan alternatif ramuan diet tinggi serat dalam industri makanan disebabkan sifat pemakanan, sifat berfungsi serta sitfat kestabilan penyimpanannya.